Doping of semiconductors by molecular monolayers: monolayer formation, dopant diffusion and applications. (January 2017) - Ye, Liang; de Jong, Michel P.; Kudernac, Tibor; van der Wiel, Wilfred G.; Huskens, Jurriaan
Abstract: The continuous miniaturization in the semiconductor industry brings electronic devices with higher performance at lower cost. The doping of semiconductor materials plays a crucial role in tuning the electrical properties of the materials. Ion implantation is currently widely used. Yet, this technique faces challenges meeting the requirements for smaller devices. Monolayer doping (MLD) has been proposed as one of the alternative techniques for doping semiconductors. It utilizes dopant-containing organic molecules and grafts them onto semiconductor surfaces. The dopant atoms are subsequently driven into the substrate by high temperature annealing. MLD has shown the capability for ultra-shallow doping and the doping of 3-D structures without causing crystal damage. These features make this technique a promising candidate to dope future electronic devices. In this review the processes for monolayer formation and dopant incorporation by annealing will be discussed, as well as the applications of MLD in device fabrication.